2012
DOI: 10.1155/2012/310467
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain after Root Canal Treatment: A Prospective Cohort Study

Abstract: Aim . To evaluate the incidence and severity of postendodontic treatment pain (PEP) subsequent to root canal treatment (RCT) in vital and necrotic pulps and after retreatment. Methodology . A prospective study. Participants were all patients ( n = 274) who underwent RCT in teeth with vital pulp, necrotic pulp, or vital pulp that had been treated for symptomatic irreversible pulpitis or who received root canal retreatment, by one clinician, during an eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 27 publications
2
52
2
7
Order By: Relevance
“…The results agreed with a previous study finding that Thermafil resulted in significantly higher levels of pain than cold lateral condensation [ 16 ]. Albashaireh and Alnegrish reported that endodontic treatment on non-vital teeth had a higher chance of developing post-obturation pain than on vital teeth [ 33 ]; however, Gotler and colleagues reported the opposite, with more post-obturation pain in vital teeth [ 48 ]. We could not find a significant association between post-obturation pain and the tooth’s vitality status.…”
Section: Discussionmentioning
confidence: 99%
“…The results agreed with a previous study finding that Thermafil resulted in significantly higher levels of pain than cold lateral condensation [ 16 ]. Albashaireh and Alnegrish reported that endodontic treatment on non-vital teeth had a higher chance of developing post-obturation pain than on vital teeth [ 33 ]; however, Gotler and colleagues reported the opposite, with more post-obturation pain in vital teeth [ 48 ]. We could not find a significant association between post-obturation pain and the tooth’s vitality status.…”
Section: Discussionmentioning
confidence: 99%
“…Ibuprofen exerts its anti-inflammatory effect via synthesis of arachidonic acid metabolites (19). Informing patients regarding the possibility of postendodontic pain and drug administration for its management can improve their trust in dentists, raise their pain threshold, and increase their tendency to seek further dental treatments (20).…”
Section: Introductionmentioning
confidence: 99%
“…Among the four different independent diagnostic factors, status of pulp and pre-operative pain were only signi cant predictors for postoperative pain. Similarly, status of pulp has an in uence on postoperative pain as stated by different studies (35,36). Flare-up and postoperative pain are dependent upon the status of the pulp.…”
Section: Discussionmentioning
confidence: 91%